2003
DOI: 10.1046/j.1442-200x.2003.01754.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding practice of infants and their correlates in urban areas of Beijing, China

Abstract: The feeding practices for most of the urban infants was found to be in accordance with the Chinese government and WHO recommendations; however, non-optimal feeding practices presenting as the early cessation of breast-feeding and the introduction of solid/semisolid foods existed. Information regarding optimal feeding practices should be disseminated to mothers and medical professionals in China, to ensure optimal infant health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 13 publications
5
32
1
2
Order By: Relevance
“…Prevalence of timely initiation of complementary feeding in this study is higher than the national prevalence (51%). The result is also higher than a study in China, and Kathmandu [3,16,17]. The finding of this study is relatively similar to West Bengal India [15] but the finding is lower than a study in Northern Ethiopia, Coastal south India, Hiwot Fana hospital Ethiopia, and Southwest Ethiopia [9,[18][19][20][21].…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Prevalence of timely initiation of complementary feeding in this study is higher than the national prevalence (51%). The result is also higher than a study in China, and Kathmandu [3,16,17]. The finding of this study is relatively similar to West Bengal India [15] but the finding is lower than a study in Northern Ethiopia, Coastal south India, Hiwot Fana hospital Ethiopia, and Southwest Ethiopia [9,[18][19][20][21].…”
Section: Discussioncontrasting
confidence: 53%
“…Less than one-third of [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] months old children met the minimum criteria for dietary diversity [8,9], and only 50% received the minimum number of meals and only 21% of children aged 6-23 months met the minimum criteria [9]. Infant formula supplementation at any age is uncommon in Ethiopia [10].…”
Section: Introductionmentioning
confidence: 99%
“…Other potential influences included mastitis and infant birth weight > 2,500 grams. [17][18][19][20][21][22] A maternal factor found to consistently have a negative or no association with breastfeeding duration was higher maternal body mass index. Hospital practices and obstetric factors that consistently had negative associations with breastfeeding duration were early postnatal discharge, giving commercial discharge packs, introduction of solids with continued breastfeeding, and introduction of formula.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22] Several other factors inconsistently showed positive associations with breastfeeding duration: having a previous child or children, positive previous breastfeeding experience, breastfeeding confidence, higher social class, higher income, higher socioeconomic status, maternal attitude towards infant feeding, having been breastfed oneself, attendance at childbirth education classes, partner's perceived preference for breastfeeding, and breastfeeding knowledge. [17][18][19][20][21][22] In hospital practice and obstetrics, there were other factors which inconsistently had positive associations such as earlier breastfeeding initiation, rooming-in, early skin-to-skin contact, and encouragement to breastfeed by a health professional. Other potential influences included mastitis and infant birth weight > 2,500 grams.…”
Section: Discussionmentioning
confidence: 99%
“…Such as maternal intention to breastfeed, earlier timing of the decision to breastfeed, increased maternal age, higher maternal education, maternal non-smoking or occasional smoking and being married or having a partner [13][14][15][16]. Several other factors inconsistently showed positive associations with breastfeeding duration: having a previous child or children, positive previous breastfeeding experience, breastfeeding confidence, higher social class, higher income, higher socioeconomic status, maternal attitude towards infant feeding, having been breastfed oneself, attendance at childbirth education classes, partner's perceived preference for breastfeeding and breastfeeding knowledge [13][14][15][16]. Other study found that smoking during pregnancy, Caesarean birth, infant's admission to the intensive care unit and maternal employment status before 6 months of infant's age were negatively associated with exclusive breastfeeding [10].…”
Section: Discussionmentioning
confidence: 99%